Formulação do método dos elementos finitos para a análise elástica linear de vigas de Timoshenko - Campos, João Victor de (2015)
This work has as purpose to analyze beam elements through Finite Element Method and its structural behavior in linear elastic range regarding to the theory proposed by Timoshenko. The discretization of the domain was carried out using elements with linear geometry, with two degrees of freedom (vertical displacement and rotation of the cross section), using approximation functions of first degree to the displacement field and rotation over the element. In order to validate the developed equation, it was created a computational algorithm that is able to carry numerical simulations of the beam structural behavior based in this theory. Finally, were presented some numerical examples comparing the results provided by the software with those founded by other authors.